Penerapan Model Contextual Teaching and Learning Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Kewarganegaraan - Nur Vathatuljanah; Arif Firmansyah; Muchdar Muchdar; Yusdin Bin. M Gagaramusu; Ryan Andhika Pratama (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to improve student learning outcomes through the application of the Contextual Teaching and Learning (CTL) learning model in Civics class IV SDN 1 Sindue. The background of this study is based on the low student learning outcomes seen from the pre-test results, where only 41.37% of students reached the Minimum Completion Criteria (KKM). This research method is a Classroom Action Research (PTK) which is carried out in two cycles, with the stages of planning, action implementation, observation, and reflection. The research sample amounted to 29 students. Data collection techniques were carried out through observation, tests, and documentation. The results showed an increase in teacher and student activities from the “good” category to “very good”. Student learning outcomes also experienced a significant increase, from 41.37% in pre-action to more than 85% in cycle II. However, there are some limitations in this study. First, the research was conducted in a single class with a relatively small sample size of 29 students, which may not be fully representative of the broader population of students in other schools or regions. Second, the study was limited to two cycles, which may not fully capture the long-term impact of the CTL model on student learning outcomes. Additionally, the research relied on specific data collection techniques, such as tests and observations, which may have limitations in capturing all aspects of student engagement and learning. Further research with a larger sample size, longer duration, and a broader range of assessment methods is recommended to better understand the effectiveness of the CTL model in improving student learning outcomes. In conclusion, despite these limitations, the application of the CTL learning model is effective in improving student learning outcomes in Civics subjects.